Do we really need cadavers anymore to learn anatomy in undergraduate medicine?. (3rd October 2018) - McMenamin, P. G.; McLachlan, J.; Wilson, A.; McBride, J. M.; Pickering, J.; Evans, D. J. R.; Winkelmann, A.
Abstract: With the availability of numerous adjuncts or alternatives to learning anatomy other than cadavers (medical imaging, models, body painting, interactive media, virtual reality) and the costs of maintaining cadaver laboratories, it was considered timely to have a mature debate about the need for cadavers in the teaching of undergraduate medicine. This may be particularly pertinent given the exponential growth in medical knowledge in other disciplines, which gives them valid justification for time in already busy medical curricula. In this symposium, the pros and cons of cadaver use in modern medical curricula were debated and audience participation encouraged.